Epigraphic Notes, Aramaic and Hebrew - Millard, A. R.
cuneiform Za-ku-ri shows ZKR should be read Zakkur, not Zakir (Zekīr) or Zekar; Scribal practice at Tell Deir ‛Alla (rulings, rubrication, word-dividers); The use of writing in ancient Israel.